A convex optimization-based inversion method for the synthesis of monopulse linear arrays - Boulos, Federico; Dall'Asta, Luca; Gottardi, Giorgio; Abdul Hannan, Mohammad; Polo, Alessandro; Salas-Sanchez, Aaron (Journal of physics. Conference series, 2020)
In this work, the design of monopulse linear arrays generating sum and difference patterns with a partially shared beam forming network is addressed as an inverse problem and solved through a suitable inversion strategy. The array tails are organized into sub-arrays controlled by amplitude weights, while the remaining array elements have two independent amplitude coefficients, one for each beam. The optimal values of both common and independent excitations are determined by means of a convex optimization technique able to retrieve the globally optimal solution whether existing. Sucli a synthesis method allows one to include user- defined upper power bounds on the secondary lobes as well as to arbitrary decide the layout (i.e., the number and the sizes of the sub-arrays) of the common part. Representative results are reported and discussed to assess the effectiveness and the efficiency of the proposed technique.